2021
DOI: 10.1037/sgd0000463
|View full text |Cite
|
Sign up to set email alerts
|

LGBTQ+ people and COVID-19: The importance of resilience during a pandemic.

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has disproportionately impacted people from marginalized communities, such as lesbian, gay, bisexual, transgender, and queer (LGBTQϩ) people, adding to existing social and economic inequities experienced by LGBTQϩ community members. Given the vulnerabilities of LGBTQϩ populations, it is important for researchers to identify pandemic-related stressors that may affect the psychological and physiological well-being of LGBTQϩ people and how coping and resilience str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 59 publications
2
37
0
4
Order By: Relevance
“…This study has provided a snapshot of the impact of the COVID-19 lockdown on the lives of older lesbians/gay women living in the UK. This was set in the context of a wider examination of LGBT+ older people's experiences, given that some studies have identified that the pandemic had potential to compound preexisting challenges and health inequalities as well as to capitalize on strategies, strengths, and resilience's of the LGBT+ aging population (Goldbach et al, 2020;Reid & Ritholtz, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study has provided a snapshot of the impact of the COVID-19 lockdown on the lives of older lesbians/gay women living in the UK. This was set in the context of a wider examination of LGBT+ older people's experiences, given that some studies have identified that the pandemic had potential to compound preexisting challenges and health inequalities as well as to capitalize on strategies, strengths, and resilience's of the LGBT+ aging population (Goldbach et al, 2020;Reid & Ritholtz, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A dearth of empirical research exists about LGBTQ resilience during the COVID-19 pandemic. We found one study to date that explored the role of resilience in the relationship between COVID-19 stressors and anxiety (Goldbach et al, 2020). Goldbach and colleagues (Goldbach et al, 2020) found that higher levels of resilience weakened the relationship between COVID-19 concerns and anxiety.…”
Section: Lgbtq Minority Stress and Resiliencementioning
confidence: 99%
“…68 Coherence with their marginal status helped build a sense of authenticity and well-being, enabling the pandemic crisis to create higher resilience levels. 69 LGBTIQ (Lesbian, Gay, Bisexual, Transgender, Intersex and Queer) Topics…”
Section: Change and Copingmentioning
confidence: 99%